Comparison of some biochemical properties of two marine fish species Euthynnus alletteratus and Siganus rivulatus in Syrian marine waters - بدران, معينة; سليمان , شيم; غانم, بسمة (Latakia University Journal -Biological Sciences Series, 2020)
In this research, we compared the protein, fat, ash and moisture ratio of the two fish species Euthynnus alletteratus and Siganus rivulatus during the spring, summer, and autumn seasons of 2019 and winter of 2020, In order to give an idea of the nutritional value of the two species studied as being of the economically desirable species because of their availability and cheap price, to study the seasonal and gender effects on the chemical composition of meat. The results showed a very close levels of moisture and ash to the tow species, where the moisture was 70.2-80.71% for S. rivulatus , while for E. alletteratus was between 73.36-78.66%, and ash was 1.23-2.8% in S. rivulatus and 1.2-2.04% in E. alletteratus. The fat was noticeably different where it was 2.98-4.4% in S. rivulatus and 0.7-2.1% in E. Alletteratus, and protein was 19.25-16.275% between S. rivulatus and between 25.21-19.57% in E. Alletteratus.